IRREGULARITIES AND THE MARKET VALUE OF COMPANIES - SANTOS,SÔNIA F. S. (2020)
ABSTRACT Purpose: To investigate the impact of the irregularities under analysis and/or judged in the sanctioning administrative proceedings of the Securities and Exchange Commission on the market value of Brazilian companies. Thus, we used the signaling theory to analyze how stakeholders interpret situations and where the available information is asymmetric and incomplete among market agents. Originality/value: The study was based on the assumption that the conviction within the scope of the regulatory body can negatively affect the company’s reputation and value. Empirical evidence indicates that irregularities affect market sentiment. On the other hand, the company can present a better market value if an effective and efficient corporate governance is established, aligning the interests of stakeholders and management. Design/methodology/approach: Information was collected with quarterly data covering the period from 2010 to 2018. Two hypotheses were tested by means of regression analysis in OLS with pooled data, panel - fixed effects and 2SLS. Findings: The results indicated that the irregularities, in the analyzed period, did not impact the companies’ market value in the estimation by MQ2E. We suggest to the chief executive officer (CEO) and the chief financial officer (CFO) that they assess the level of corporate governance of their companies and invest in the search for excellence since the best levels of governance bring a positive signal to the market. The CEO is advised to pay attention to the fact that good governance is not enough to keep companies from being irregular.